The Impact Of Urbanization OnEducational Landuse In Suleja, Niger State, Nigeria - Abubakar, Adamu; Bala, Adamu; Samuel David, Shidali; Abdullahi, Habib; Kodan, Yisa Moses (Journal of Social Transformation and Regional Development, 2022)
ABSTRACT Urbanization has impacts on social change and modernization which are parts of a continuum rather than empirically separate issues. Suleja has been surrounded with growing settlements whose influence constantly threatens the infrastructural facilities. There has been difficulty monitoring the extent and rapidity of the changes occurring within the area. The research aimed to assess the changes in educational landuse in Suleja between 2009 and 2019 and also to identify the magnitude of the change. 375 questionnaires were administered in a proportion of interval of houses based on arrangement in the study area to acquire the socio-economic characteristics of the area. Population data was also used to analysis growth pattern(s) in the area and field survey was carried to ascertain the numbers of schools in the study area. It was discovered that 4708sqm of land was used for educational purpose as at 2000 and there was an increase to 8552sqm as at 2012 and 127431.8sqm in 2019. The study also noted that majority of schools within the residential areas are private owned. It also noted that majority of private own school were within the residential areas. It was therefore recommended that a New Master Plan for Suleja should be developed because the only available one was developed in 1986.